Cinematic narration and its psychological impact : functions of cognition, emotion and play - Wuss, Peter (Cambridge Scholars, 2009)
Film provides experience potential. Contemporary cognitive psychology gives the opportunity to define this impact on the film spectators' mind in regard to different aspects of cognition, imagination and emotion. Proceeding from these positions, this book.